Comparative analysis of studies of speed variations within a breasstroke cycle - Tourny, C.; Chollet, D.; Micallef, J. P.; Macabies, J. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
The analysis of the speed variations within a breaststroke cycle gives information about the manner in which the different phases of the cycle contribute to swimmer's movement. This study underlines the technical changes in the breaststroke during the last fifteen years and compares the recordings of the speed variations with the curve of the women's 100 m breaststroke champion in the Seoul Olympic Games 1988.